(3cJGH ajg CSeGA Gdecfjjf ef QLGd GdUMjMjfs - (3eMeO Hf gGQhf GdeZQHjs
(3ChdgG (B:s
(3CHh EHQGgje YHO Gddg Hf CHj Chai ESeGYjd Hf LYaQ GdCfUGQi s
(3BNQgG (B:s
(3CHh bdjT ehdi YeQh Hf GdYGU CHh SajQ bjd GSeg bReGf ehdi GHf CHj CMeO BNQg GdMeO ddg QH GdYGdejf hUdhGJg Ydi SjOfG eMeO hYdi Bdg hUMHg hSdGeg MSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GdhGQO MOjKkG s
Keywords: (3GdJGQjNs